2015
DOI: 10.1111/tbed.12327
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Comparative Epidemiology of Avian and Human Influenza A H5N1 and H7N9 - Lessons and Unanswered Questions

Abstract: SummaryThe aim of this work was to explore the comparative epidemiology of influenza viruses, H5N1 and H7N9, in both bird and human populations. Specifically, the article examines similarities and differences between the two viruses in their genetic characteristics, distribution patterns in human and bird populations and postulated mechanisms of global spread. In summary, H5N1 is pathogenic in birds, while H7N9 is not. Yet both have caused sporadic human cases, without evidence of sustained, human-to-human spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 136 publications
(167 reference statements)
5
64
0
1
Order By: Relevance
“…Avian influenza A(H7N9) virus has been detected mainly in poultry from LPM, which therefore are considered important drivers of the zoonotic infections. This was confirmed by the observed reduction in human infections following temporary closure of LPM (Bui et al., ; Wu et al., ). However, only 6 per cent of the 139 confirmed H7N9 patients detected before 1 December 2013 were poultry workers, suggesting that other modes of transmission may apply, including infection after contact with persons with mild illness (Li et al., ).…”
Section: Introductionmentioning
confidence: 64%
“…Avian influenza A(H7N9) virus has been detected mainly in poultry from LPM, which therefore are considered important drivers of the zoonotic infections. This was confirmed by the observed reduction in human infections following temporary closure of LPM (Bui et al., ; Wu et al., ). However, only 6 per cent of the 139 confirmed H7N9 patients detected before 1 December 2013 were poultry workers, suggesting that other modes of transmission may apply, including infection after contact with persons with mild illness (Li et al., ).…”
Section: Introductionmentioning
confidence: 64%
“…However, exposure details are missing for a large proportion of cases (see Additional file 1: Table S1 and [3, 7]). We have shown that a history of close poultry contact is far more common for human H5N1 cases than H7N9 cases [7].…”
Section: Resultsmentioning
confidence: 99%
“…For all zoonotic avian influenza virus AIV serotypes except H5N1 and H7N9 (for which methods have been previously described ([3]), we reviewed epidemiological features of outbreaks or cases. We searched publications using the Scopus database, and grey literature using the World Health Organisations (WHO), Centres for Disease Control and Prevention (CDC), Flutrackers and ProMed websites, using the subtype as the keyword.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pandemic influenza outbreaks of HPAIV in poultry pose significant threats to public health, as highlighted by the emergence of HPAIV H5N1 (Ferguson et al, 2004); thus, pandemic preparedness is a global priority to combat these threats. The HPAIV H5N1 first emerged in Hong Kong in 1997 with direct transmission from chickens to humans, and then re-emerged in Mainland China in 2003 (Bui et al, 2016). This infection leads to an acute respiratory distress syndrome (ARDS), the destruction of inflamed lung tissues, and an overwhelming inflammatory response, known as the “cytokine storm,” releasing numerous cytokines, such as interleukin-1 (IL-1), IL-6, tumor necrosis factor-α (TNFα), and other cytokines, which have been linked to fatal outcomes in humans (Subbarao et al, 1998; Ku and Chan, 1999; Chan, 2002; de Jong et al, 2006; Kash et al, 2006; Xu et al, 2006; Kobasa et al, 2007; Kawachi et al, 2009; Uyeki, 2009; Zhou and He, 2009; Li et al, 2010).…”
Section: Introductionmentioning
confidence: 99%